Cemaran Mikrobiologis Pada Beberapa Loloh Bali Di Kota Denpasar - Putu Ari Sandhi Wipradnyadewi; Ni Luh Ari Yusasrini (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2017)
The purpose of this study was to determine the amount of microbial contamination andbacterial pathogens as well as the level of safety on some of loloh Bali in Denpasar. Thestudy consisted of two phases i.e. first: an inventory of some loloh Bali in Denpasar, amongothers, loloh don base, loloh don sirsak, loloh don jarak, loloh samiloto, loloh dontempuyak, loloh kunyit, loloh temulawak and loloh don piduh. The second stage: the analysisof microbial contamination and bacterial pathogens of loloh BaliIn the first stage concluded that there were loloh don base, loloh don sirsak, loloh don jarak,loloh samiloto, loloh don tempuyak, loloh kunyit, loloh don piduh and loloh temulawak inDenpasar. The second phase resulted that 100% of the samples loloh don base, don piduh,don sirsak, don jarak, and don tempuyak compliant with the value of total microbes, 16.7%of the samples loloh samiloto, 75% loloh kunyit and 50% loloh temulawak meet therequirements of total microbes. 100% of loloh don piduh, 16.7% loloh don base, 0% lolohsamiloto, 0% loloh don sirsak, 0% loloh don jarak, 0% loloh don tempuyak, 75% lolohkunyit and 50% loloh temulawak meet the requirementsof total coliform and 100% of thesamples have been analyzed showed did not contain E.coli. Loloh don base 4, loloh kunyit2, loloh kunyit 4, loloh don piduh meet all the requirements of total microbes, coliform andE. Coli.